Curriculum and teaching dialogue. volume 23, - Bohan, Chara Haeussler; Pecore, John L.; Allaire, Franklin S. (Curriculum and teaching dialogue ;, 2021)
Curriculum and Teaching Dialogue is a peer-reviewed journal sponsored by the American Association for Teaching and Curriculum. The purpose of the journal is to promote the scholarly study of teaching and curriculum. The aim is to provide readers with knowledge and strategies of teaching and curriculum that can be used in educational settings. The journal is published annually in two volumes and includes traditional research papers, conceptual essays, as well as research outtakes and book reviews. Publication in CTD is always free to authors.